GPU Accelerated Numerical Simulation of Local Scours Near Hydraulic Structures (London Journal of Engineering Research, 2022)
A module of sediments transport allowing to simulate the dynamics of local bed scours in proximity to hydraulic structures has been integrated into the three-dimensional non- hydrostatic multilayer open flow model. The sediment transport calculation is performed based on the formulas that apply the value of bed-shear stress. The slope slide in the scour hole and the alteration of the critical shear stress depending on the local bed inclination and flow speed direction are taken into account. This numerical model has been implemented completely by means of a GPU which allows to perform complicated 3D calculations within a reasonable time period. The results of testing performed based on the publicly available experimental data are given: comparison of the dynamics of bed transformation behind the apron as influenced by jet current is performed; development of local scours in proximity to the vertical circular pile is validated based on the results of large-scale experiments.
Keywords: geomagnetic storms / sunspot number (ssn)/ communications; navigation; surveillance (cns) and satellite solar outage; Barium Nickel Ferrite; FTIR Spectra; Debye temperature; Force constants; Local scours; GPU calculations; non-hydrostatic; OpenCL; sediment transport; three-dimensional multilayer model